The dynamic compressive behavior and constitutive models of a near α TA23 titanium alloy. (December 2021) - Yu, Weixin; Li, Yue; Cao, Junhui; Yang, Zhijun; Zhang, Jinyong; Lang, Shaoting
Abstract: The dynamic impact tests were carried out for a near α TA23 titanium alloy in deformation temperature range 293 K–773 K and strain rate range 0.001 s −1 -4000 s −1 . The test results show that as deformation temperature increases, the flow stress decreases significantly, and the temperature and strain rate have an interactive effect in the dynamic impact compression process. The original Johnson-Cook (J-C) model and its modified model were established. The model verification results show that the relative error of the modified model is 3.28%, while the relative error of the original model is 5.32%, which indicates that the modified model has higher accuracy and applicability in predicting the dynamic impact deformation behavior of TA23 alloy.